Koncertna dejavnost Festivala Ljubljana: 1953-1963 - Ribizel, Tjaša (Muzikološki zbornik, 2010)
Festival Ljubljana was founded in 1953, in order to promote Slovenian and Yugoslav culture and to extend the cultural season in summer. In the first ten years there were 125 music performances, conducted by Yugoslav and foreign artists. Concerts improved during the first ten years and every programme period (1953, 1954-1959, 1960-1963) represented an improvement on the previous one.
Keywords: concert repertoire; Festival Ljubljana; glasbene prireditve; koncertni repertoar; music concerts